If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y = -2(y + 1) Reorder the terms: 9y = -2(1 + y) 9y = (1 * -2 + y * -2) 9y = (-2 + -2y) Solving 9y = -2 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. 9y + 2y = -2 + -2y + 2y Combine like terms: 9y + 2y = 11y 11y = -2 + -2y + 2y Combine like terms: -2y + 2y = 0 11y = -2 + 0 11y = -2 Divide each side by '11'. y = -0.1818181818 Simplifying y = -0.1818181818
| 9x-42=2x | | 8y-15y+7= | | -2(-4z)=64 | | 3x+7y= | | 2(5z)=-80 | | 10b^2-8b-7=0 | | x+43=38 | | -11m+6m=11-31 | | -5(3p+4)-25=3(2p+6) | | 2(c-6)=3(c-7) | | 8-6n+2n=43-95 | | 2y-4(2y+4)=-4-2(-1-y) | | 2(0)+6=y | | (2x+4)(5x-6)= | | 29=5-3h | | 4*-3+7= | | 4*-3=7 | | 2(5z-1)-5(z+2)=2(z+1) | | 5+2n-4=5n+2-2n | | -14=-7t | | 10p-11=-2p+7 | | 3.5q-2.7-3.9q=-1.4q-5.2 | | 2(3x-4)-(2x-4)= | | 45-23=x | | 25x-30x-16=0 | | -16-9-2= | | 4(x+15)=17x | | -4y+8=5y+9 | | -4(-2+5)= | | 5t^2+14x+3=0 | | 6y+8y=98 | | 15+2(9-6)+9= |